1999
DOI: 10.1016/s0022-2860(98)00943-0
|View full text |Cite
|
Sign up to set email alerts
|

XPS investigation of thin SiOx and SiOxNy overlayers

Abstract: Angle-resolved XPS is used to determine the thickness and the uniformity of the chemical composition with respect to oxygen and nitrogen of the very thin silicon oxide and oxynitride overlayers grown on silicon. ᭧

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
3
3
0
Order By: Relevance
“…The other three peaks (A, B and C) centered around 101.4 eV, 102.7 eV and 103.6 eV are attributed to Si 3 N 4 , SiN x O y and SiO 2 respectively. The binding energy of the peaks assigned to Si 3 N 4 , SiN x O y and SiO 2 matches quite well with the studies reported earlier [16][17][18][19][20]. The presence of both SiN x O y and SiO 2 peaks in Si 2p spectra clearly shows the incorporation of oxygen in all samples.…”
Section: Resultssupporting
confidence: 89%
“…The other three peaks (A, B and C) centered around 101.4 eV, 102.7 eV and 103.6 eV are attributed to Si 3 N 4 , SiN x O y and SiO 2 respectively. The binding energy of the peaks assigned to Si 3 N 4 , SiN x O y and SiO 2 matches quite well with the studies reported earlier [16][17][18][19][20]. The presence of both SiN x O y and SiO 2 peaks in Si 2p spectra clearly shows the incorporation of oxygen in all samples.…”
Section: Resultssupporting
confidence: 89%
“…It is well established that the oxide side of the interface is positively charged as the result of electron injection to the silicon side for any type of silicon, as schematically shown in Figure . , Hence, as was already advocated in our previous publication, the overall band-bending is additive (p-type + oxide), resulting in a larger shift (∼0.5 eV) upon illumination . The absence of significant photoshift for the n-sample, can also be attributed to compensation of the surface upward bending of the n-Si by the oxide downward bending at the interface, as schematically shown in Figure b.…”
Section: Discussionsupporting
confidence: 61%
“…Upon introduction to the spectrometer, electrons flow from the n-type and holes from the p-type Si wafers so that they are charged differently, due to doping. However, the charges on the surfaces are screened by band bending and by accumulation of opposite-sign charges near the surface. When light of energy greater than the band gap of Si is incident on the sample charge carriers return the bands to the flat-band condition. This data was collected with neutralizer off. We also modulated (not shown here) the electrical potential of the surface using an external power supply generated square waves of ±10 V amplituted and at frequencies from 0.5 to 500 Hz, with no observable effect on the shifts due to the incident light.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SiC XPS peak was not found for sample 4 after treatment. Instead, SiO2 was detected at binding energies 103.3±0.2 eV and 105 eV showed all silicon oxidized[118,119].…”
mentioning
confidence: 97%